Development of Performance Index for Onion Seed Extractor - Singh, Raghuraj; Mani, Indra; Rai, Anil (Journal of Agricultural Engineering, 2010)
A mechanical onion seed extractor was evaluated to study the effects of operational variables on seed quality parameters, and a performance index was developed for using principal component analysis method that proved to be a tool to select best design and operational variables. The concave clearance marginally affected vigour index, and the average values were 30.27, 30.70 and 29.63 per cent. However, the average vigour index was 29.89, 28.97 and 31.74% at the cylinder speed of 3, 4 and 5 m/s, respectively. The best performance combination with performance index of 1.0 was obtained for spike tooth mechanism, with concave clearance of 4.5 mm and cylinder speed of 5 m/s. The performance indices were categorized as high (1-6), moderate (7-24) and low performance (25-27) for onion seed extractor. The best combination with highest value of performance index was obtained with spike tooth extraction mechanism (E1), 4.5 mm concave clearance (C3) and 5 m/s cylinder speed (S3).